Socio-environmental disasters on Brazilian soil – is it possible to avoid them when the issue is associated with urban waters? - Hidalgo Junior, Massaguer; Soto, Gabriella Rodrigues Bertero; Araujo, Eloisa Carvalho de (National Journal of City Management, 2025)
Objective – To discuss the issue of socio-environmental disasters, exploring their relationship with urban waters and emphasizing the importance of safeguarding water and sanitation systems in the face of climate change, with the goal of promoting healthy and prosperous cities. Methodology – Based on theoretical, documentary, and informational readings, adopting an exploratory approach that brings together perceptions, reflections, and experiences on territorial planning and urban management in the context of socio-environmental risks and problems. Originality/relevance – The study is situated in the context of addressing climate and environmental crises, tackling the theoretical gap regarding the integration of urban waters as a central element in territorial planning and in mitigating socio-environmental risks, while articulating dimensions of life, education, landscape, and socio-environmental justice. Results – The analysis pointed to the need for planning strategies that incorporate, in an articulated manner, instruments capable of responding to the challenges posed by extreme events and socio-territorial inequalities, fostering a culture of care and new ways of living in cities. Theoretical/methodological contributions – Expands the understanding of integrated urban-environmental planning with urban waters as a structuring component, providing inputs for new interdisciplinary approaches and for the incorporation of socio-environmental indicators into decision-making processes. Social and environmental contributions – Suggests pathways for public policies that prioritize socio-territorial equity, urban resilience, and the protection of water systems, promoting concrete improvements in quality of life and environmental balance in cities.